Implementation Strategy of IT Employee Onboarding at the Center for Education Data and Information Technology, Education Office of DKI Jakarta Province - Mufti, Raja Gantino; Giyanto, Bambang; Rivai, Firman Hadi (Neo Journal of economy and social humanities, 2025)
This study aims to analyze the onboarding process of new IT employees at the Center for Education Data and Information Technology (UPT Pusdatin Pendidikan), under the Education Office of DKI Jakarta Province. The study further examines the factors influencing the success of IT employee onboarding and identifies strategies for implementing effective onboarding practices. A qualitative research approach was employed, with data collected through interviews and document analysis. Data analysis involved data collection, reduction, presentation, and conclusion drawing. The findings reveal that the onboarding process for IT employees at UPT Pusdatin is still passive and poorly structured. This is evident from the lack of formal training, absence of written guidelines, and a reliance on individual initiative for adaptation. Four main factors influencing onboarding success were identified: self-efficacy, role clarity, social integration, and knowledge of organizational culture. These aspects face ongoing challenges due to limited organizational support, suboptimal communication, and the lack of a formal socialization system. To enhance onboarding effectiveness, a shift toward a more proactive, systematic, and sustainable approach is recommended. The proposed strategies include the development of structured onboarding programs, implementation of mentoring or buddy systems, regular evaluations with two-way feedback, and activities fostering social and cultural integration within the organization. Successful implementation of these strategies requires strong commitment from UPT leadership to consistently welcome, support, and guide new employees to enable quick adaptation and meaningful contribution in the workplace.